The role of underutilized crops in alleviating hidden hunger - Kumssa, Diriba (2017)
The quantity, quality and variety of food ingested by humans largely determines the intake of the essential mineral micronutrients required for normal human physiological functioning, growth and development. Inadequate dietary intake, low bioavailability, and failure of the human body to utilize ingested essential minerals lead to mineral micronutrient deficiencies (MNDs), an invisible form of undernutrition also known as hidden hunger. With the aim of aiding future human nutrition policy planning, the extent of dietary MNDs of calcium (Ca), copper (Cu), iodine (I), iron (Fe), magnesium (Mg), selenium (Se) and zinc (Zn) were estimated by integrating food supply and composition, estimated average requirement and demographic data. National level dietary Ca, Mg and Zn deficiency risks between 1992 and 2011 were estimated for the populations of 145 countries. Globally, in 2011, 3.5 and 1.1 billion people were at risk of Ca and Zn deficiency, respectively, due to inadequate dietary supply; 14 million people were at risk of Mg deficiency during the same period. Ninety percent of those at risk of Ca and Zn deficiency in 2011 lived in Africa and Asia. Considering the limited policy-making relevance of the low resolution national estimates of mineral MNDs, sub-national level assessments of the prevalence of dietary mineral MNDs were made for Malawi in 2011 using a 7-day household dietary recall survey data (n = 12117). It was estimated that >50% of households in Malawi were at risk of energy, Ca, Se, or Zn deficiencies due to inadequate dietary supplies, but supplies of Fe, Cu and Mg were adequate for >80% of households. Interventions to address dietary mineral deficiencies, such as dietary diversification using underutilized multipurpose and hardy tree/shrub species (e.g. Moringa spp.), were considered. Greater than 78% of Moringa growing households in southern Ethiopia and Kenya use M. oleifera (MO) and M. stenopetala (MS) trees as a source of food. Increasing the dietary consumption of MO and MS leaves, as a fresh vegetable or in powdered form, can reduce the prevalence of mineral micronutrient deficiencies, most notably Se deficiency. Daily consumption of 100 g Kenyan MO or MS fresh leaves could provide 100% and 144%, respectively, of the Se recommended daily allowance for a healthy adult man. Research and development to promote the use of these species in the fight against hidden hunger, are necessary. Continuing to reduce mineral MND risks through dietary diversification, and food and agricultural interventions, including fortification, crop breeding and use of micronutrient fertilisers, will remain a significant challenge during the global Sustainable Development era.